O PRONATEC no sistema de ensino brasileiro: estudo de caso no Instituto Federal de Goiás nos municípios de Goiânia e Aparecida de Goiânia - Souza, Vanessa Alexandre de (2020)
This thesis has as its main theme; the impact of the - Programa Nacional de Acesso ao Ensino Técnico e Emprego - (PRONATEC) in Goiania and metropolitan region. We seek to analyze the scope of its goals and the concrete facts resulting from this educational policy that defines itself as the largest investment in Technical and Professional Education developed in Brazil. Our main objective is to comprehend the relationship between work and education in the Brazilian educational system and the logic of its proposals developed by the official bodies in the scope of professional and technical education. Brazilian educational system was organized attending the logic of exclusion and social inequalities. We focus our analyses on how the professional education characterizes itself in the Brazilian teaching system. Our field of search was at Instituto Federal de Educação, Ciência e Tecnologia (IFG) at Campus Goiânia and at Campus Aparecida de Goiania. The Instituto Federal de Educação, Ciência e Tecnologia (IFG) in partnership with PRONATEC coordinated the offer of courses after August, 2012. In this work we present data from the courses offered since 2013. We conducted semi-structured interviews with graduated students of the courses, collecting information about their educational trajectory, narratives about their experiences in taking a technical course and their social reality. We collected testimonials, questionnaires and general data about the students. As main theoretical framework we used the of Gramcian concept of unitary and polytechnic school, the ideal model to technical and vocational education. The failures, difficulties and contradictions presented by educational policies like PRONATEC are related to the capitalist social structure and to the social of division of labor. In the capitalist production mode, education is articulated with the division of labor maintaining the reproduction of the inequalities by the educational system.